Best Practice, Implementasi Gerakan Literasi Siswa Dalam Pembentukan Karakter “ MEKAR-BERSERI” - Julia Damaris Bukit (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2019)
Reading is a window to the world, but the level of interest in reading in Indonesia is very low. This is exactly what encourages the writer to create a literacy program in schools in accordance with the GLS program that is required to be done. Reading and writing can reduce student problems and can even solve problems that are being faced by students. Students who are diligent in reading and writing will certainly have high discipline. In accordance with the vision and mission and the motto of SMP Negeri 3 Barusjahe, students are expected to be able to realize